Dexamethasone and postoperative capillary glucose levels in type 2 diabetes mellitus - Elliza R,; Nadia Md Nor,; Azlina M,; Yeoh CN,; Maryam B,; Hanita O, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Perioperative intravenous (IV) dexamethasone is administered prophylactically for post operative nausea and vomiting. However, its glucocorticoid property which raises blood glucose is of concern, especially among diabetic patients. The surgical stress response also contributes to increased perioperative blood glucose. Prior studies showed higher glucose levels with dexamethasone 8 mg compared to 4 mg, hence we studied the effect of the lower dose amongst diabetic patients. This prospective, single blinded, randomised study recruited forty-six type 2 diabetes mellitus patients planned for surgery under general anaesthesia. They received IV dexamethasone 4 mg or saline (placebo) after induction of anaesthesia. Capillary blood glucose levels were recorded preoperatively, and subsequently at recovery (T0), and at 6, 12, 18 and 24 (T6, T12, T18, T24) hours post-operatively. Median glucose levels were higher at 9.0 [10.5-7.7] mmol/l in the dexamethasone group, versus 7.4 [9.2-5.9] mmol/l in the placebo group at T0, p = 0.022. Similarly at T6, the dexamethasone group recorded higher glucose levels of 11.2 [15.0-9.3] mmol/l, versus 7.7 [9.0-6.2] mmol/l in the placebo group, p = 0.001. This corresponded to a significant difference between the groups, in the change of glucose levels from baseline values, p = 0.042. Subsequent readings at T12, T18, and T24 were comparable between the groups. In conclusion, IV dexamethasone 4 mg in type 2 diabetic patients, resulted in higher glucose levels immediately postoperative and 6 hours later. The change in blood glucose from baseline levels was significant between the groups at 6 hours postoperatively. Glucose levels however remained within acceptable range of approved guidelines in both groups at all recorded intervals.